Hypertension control at hospital discharge after acute coronary event: influence on cardiovascular prognosis—the PREVENIR study. Issue 6 (1st December 2002) - Amar, J; Chamontin, B; Ferriéres, J; Danchin, N; Grenier, O; Cantet, C; Cambou, J-P
Abstract : Objective: To assess hypertension control in patients admitted to hospital for an acute coronary event and to investigate the influence on prognosis of controlling hypertension before hospital discharge. Design: Multicentre retrospective cohort study. Methods: The medical records were examined of all patients admitted in 77 cardiological centres on January 1998 for myocardial infarction or unstable angina and who survived. Clinical characteristics, blood pressure at hospital discharge, and cardiovascular events during a six month follow up were recorded. Main outcome measures: Cardiovascular deaths and non-fatal myocardial infarction. Results: Data were available in 1247 patients. At discharge, 411 (32.9%) had uncontrolled hypertension; among these, 276 (22.1%) were uncontrolled on the basis of systolic blood pressure alone. Forty three cardiovascular deaths and 20 non-fatal myocardial infarcts occurred during follow up. In a multivariate analysis, age, left ventricular ejection fraction, previous history of cardiovascular disease, and isolated systolic hypertension (odds ratio 1.9, 95% confidence interval 1.07 to 3.37) were associated with the outcome. Conclusions: 22.1% of patients admitted to hospital for an acute coronary syndrome have uncontrolled isolated systolic hypertension on discharge. This appears to be an independent predictor of cardiovascular outcome.